The acute effects of vibration training on balance and stability amongst soccer players. Issue 1 (2nd January 2016) - Cloak, Ross; Nevill, Alan; Wyon, Matthew
Abstract: Acute whole body vibration training (WBVT) is a tool used amongst coaches to improve performance prior to activity. Its effects on other fitness components, such as balance and stability, along with how different populations respond are less well understood. The aim of the current research is to determine the effect of acute WBVT on balance and stability amongst elite and amateur soccer players. Forty-four healthy male soccer players (22 elite and 22 amateur) were assigned to a treatment or control group. The intervention group then performed 3 × 60 seconds static squat on vibration platform at 40 Hz (±4 mm) with Y balance test (YBT) scores and dynamic postural stability index (DPSI) measured pre and post. DPSI was significantly lower in the elite players in the acute WBVT compared to amateur players ( F 1, 40 = 6.80; P = 0.013). YBT anterior reach distance showed a significant improvement in both amateur and elite players in the acute WBVT group ( F 1, 40 = 32.36; P < 0.001). The improvement in DPSI amongst the elite players indicates a difference in responses to acute high frequency vibration between elite and amateur players during a landing stability task. The results indicate that acute WBVT improves anterior YBT reach distances through a possible improvement in flexibility amongst both elite and amateur players. In conclusion, acute WBVT training appears to improve stability amongst elite soccer players in comparison to amateur players, the exact reasoning behind this difference requires further investigation.